Offene Reposition und Schrauben‑/Plattenosteosynthese von Fingergrundgliedfrakturen - Unglaub, Frank; Langer, Martin Franz; Löw, Steffen; Hohendorff, Bernd; Spies, Christian (Operative Orthopädie und Traumatologie, 2019)
ObjectiveAnatomical open reduction and internal fixation using screw/plate osteosynthesis.IndicationsExtra-articular fractures with clinically evident malrotation of the finger, comminution fracture and/or loss of length, which cannot be treated non-operatively; fracture instability; intra-articular fracture with step off greater than 1 mm, which cannot be treated percutaneously but openly using plate/screw osteosythesis; failure of conservative treatment.ContraindicationsGeneral operative limitations.Surgical techniqueDorsal, mediolateral, or palmar approach, temporary reduction using pincers or optional Kirschner wires; screw/plate osteosynthesis for internal fixation.Postoperative managementImmediate mobilization facilitated by buddy loops for the first 4-6 weeks, prevention of edema using elastic dressing, physiotherapy.ResultsOpen reduction and internal fixation using screw/plate osteosynthesis provides good results in combination with immediate mobilization. Nevertheless, adhesion of tendons or capsule tissue with restriction of range of motion is observed.